A Comparison of Energy Consumption between Low-E Glass and Standard Float Glass Window - Mohamed, Juliana (Multidisciplinary Applied Research and Innovation, 2023)
Glass is playing more important role in architecture industry and our daily life, also it undertakes much important function. The sunshine transmittance of the common glass is very high, and the infrared reflection rate is low, so most of the sunshine passes through the building glass. As a result, the indoor temperature rises and the energy of the indoor objects radiates out through the glass, which brings out the waste of energy. For this project, here are two different types of glass and their subcategories, each with its own uses and advantages that is Float Glass VS Low-E Glass. The aim of this research is to identify does the Low-E glass reduce the energy consumption through out the year. To achieve this research, KKTM Sri Gading’s library will be model by using two different material glass window and for analysing the model energy usage using software Autodesk Insight and Autodesk Green Building Studio. A literature review, study the material properties, 3D modelling, analyse and comparing the glass and eventually the drafting of the study report are all part of the project.